Memaknai Cinta dan Kehilangan Melalui Puisi “Cinta yang Agung” Karya Kahil Gibran dengan Pendekatan Struktural - Bunga Nur Eidies Septiananta (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
Poetry is one of the literary works that has lines and stanzas consisting of several choices of words that contain meaning so as to produce a series of sentences that are beautiful, charming, heartfelt and contains deep meaning. Poetry is also a form of expression of feelings from the poet which is a description of the surrounding environment. This affects the poet in creating his work, one of which is about love, love is something human that is experienced by every person on this earth. Sometimes love does not always go as desired, everyone must feel lost for various reasons. In this case, how do we interpret love and loss from the perspective of a poet. This research will dissect Kahil Gibran's poem titled Cinta yang Agung which aims to find and explore more about love and loss by dissecting the structure in the poem. The research uses a structural approach which results in knowing how the concept of love and loss is viewed from the physical and inner structure of the poem. And from the poem we can learn how to learn to be sincere and let go to reach a free and spacious heart.